2012
DOI: 10.1186/1756-0500-5-283
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and tolerability of donepezil 23 mg in patients with moderate to severe Alzheimer’s disease

Abstract: BackgroundDonepezil (23 mg/day) is approved by the US Food and Drug Administration for the treatment of patients with moderate to severe Alzheimer’s disease (AD). Approval was based on results from a 24-week, randomized, double-blind study of patients who were stable on donepezil 10 mg/day and randomized 2:1 to either increase their donepezil dose to 23 mg/day or continue taking 10 mg/day. The objective of this study was to assess the long-term safety and tolerability of donepezil 23 mg/day in patients with mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…two subgroups were defined in the study: patients who had received donepezil 10 mg (10 mg/23 mg subgroup) and those who had received donepezil 23 mg (23 mg/23 mg subgroup) in Farlow's double-blind study. 9 For the purposes of this extension study, all participants would be placed on donepezil 23 mg. When compared with the 23 mg/23 mg subgroup, the 10 mg/23 mg subgroup had higher rates of cholinergic AEs during the first four weeks of the trial.…”
Section: Donepezil 23 Mg: Efficacy and Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…two subgroups were defined in the study: patients who had received donepezil 10 mg (10 mg/23 mg subgroup) and those who had received donepezil 23 mg (23 mg/23 mg subgroup) in Farlow's double-blind study. 9 For the purposes of this extension study, all participants would be placed on donepezil 23 mg. When compared with the 23 mg/23 mg subgroup, the 10 mg/23 mg subgroup had higher rates of cholinergic AEs during the first four weeks of the trial.…”
Section: Donepezil 23 Mg: Efficacy and Safetymentioning
confidence: 99%
“…Consequently, 17.5% versus 11.4% of patients discontinued therapy as a result of AEs in the 10 mg/23 mg and 23 mg/23 mg subgroups, respectively. 9 The investigators concluded that the difference in discontinuations between groups was a result of the transient increase in cholinergic-related AEs that occur with titrating from a lower-to a higher-dose regimen. 9 onset of new AEs was limited to the initial weeks of the study and declined thereafter.…”
Section: Donepezil 23 Mg: Efficacy and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Different classes of AchE inhibitors, including tacrine, donepezil, rivastigmine, galantamine, xanthostigmine, para-aminobenzoic acid, coumarin, flavonoid, and pyrrolo-isoxazole analogues, have been developed for the treatment of AD. Among them, donepezil hydrochloride (DPH) is the second FDA-approved anti-AD drug and is considered a safe and well-tolerated drug for AD patients [7,8]. DPH has a very long half-life, indicating that it is ideal for convenient once-daily dosage [3,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent 12-month, open-label extension study, in which all participants received donepezil 23 mg/day, has also been conducted. Several articless and presentations have detailed either the primary outcomes from these trials or outcomes from post hoc analyses of trial data [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%